Emotion and schools understanding how the hidden curriculum influences relationships, leadership, teaching, and learning - Newberry, Melissa; Gallant, Andrea; Riley, Philip (Bingley, U.K. : Emerald, 2013)
Emotion in Schools: Understanding How the Hidden Curriculum Influences Relationships, Leadership, Teaching, and Learning reports the history, developments, applications and possible future directions of relational and emotion-focused school research from North America, Asia-Pacific and Europe. It begins by scoping the field from both a psychological and sociological perspective. The chapters frame the key debates in the research literature while adding the unique perspective of experts from the field, before honing in on the school: the administration context, teacher context and student context. The book explores the contests within the field, including psychological and socio-cultural knowledges, individual and collectives, emotions as inputs/outcomes, and the false binary of emotions and rational thought. The middle sections of the book take these perspectives into the field to see how they operate in schools. First, methods for identifying and responding to emotion and relationships in schools are presented. Second, the positive and negative products of emotions and emotion work are outlined and their effects on relationships and school functioning are discussed. The book provides readers with new insights into the hidden curriculum. It offers new ways of working with emotion in a variety of relationships for positive outcomes: the selection and induction of teachers; the role of emotions in leading; emotional and emotion learning; and, the inter-relationship between emotions, school culture, classroom and staffroom dynamics.
The enchanted loom / Bernie Neville -- The demand of multiplicity in the classroom : emotion regulation and cognitive load / Melissa Newberry -- Emotions in education policy : a social contract analysis of asymmetrical dyads and emotion / Shaun Rawolle -- Organisational position and social-professional relationships in schools : an exploratory study of teacher leaders work life in Flanders / Charlotte Struyve, Geert Kelchtermans -- The emotional labour of the aspirant leader : traversing school politics / Andrea Gallant, Philip Riley -- Life on school landscapes : teachers' experiences, relationships and emotions / Cheryl J. Craig -- Learning to teach and the false apprenticeship : emotion and identity development during the field experience placement / Shawn Michael Bullock -- The interpersonal dimension in the classroom : a model of teachers' interpersonal role identity, appraisal and teacher-student relationships / Perry den Brok ... [et al.] -- Self-conscious emotion : how two teachers explore the emotional work of teaching / Andrea Gallant -- Technology-mediated caring : building relationships between students and instructors in online k-12 learning environments / Jered Borup, Charles R. Graham, Andrea Velasquez -- Classroom management : a pathway to improving school climate in two British secondary schools / H.Jerome Freiberg, Stacey M. Templeton, Sabra Helton -- Types of professional and emotional coping among beginning teachers / Paul W. Richardson, Helen M.G. Watt, Christelle Devos -- A reflection on the place of emotion in teaching and teacher education / Anita Woolfolk Hoy -- Afterword : the teaching fantasia / Melissa Newberry, Andrea Gallant, Philip Riley.
Keywords: Education -- Classroom Management; Education -- Organizations & Institutions; Teaching staff; Schools; Educational psychology; Teacher-student relationships -- Psychological aspects; Emotions; Learning, Psychology of